Metal-free synthesis of 3-methylthiofurans from homopropargylic alcohols and DMSO via a tandem sulfenylation/cyclization reaction in a one-pot manner. Issue 12 (6th October 2016) - An, Zhenyu; She, Yue; Yang, Xiaodong; Pang, Xiaobo; Yan, Rulong
Abstract : A tandem sulfenylation/cyclization reaction for the synthesis of 3-methylthiofurans from homopropargylic alcohols and DMSO in a one-pot manner has been developed. Abstract : A tandem sulfenylation/cyclization reaction for the synthesis of 3-methylthiofurans from homopropargylic alcohols and DMSO in a one-pot manner has been developed. DMSO as a methylthiolation agent has been used for C–S bond formation in this process. Homopropargylic alcohols with various substituted groups proceed smoothly and the desired 3-methylthiofurans are obtained in moderate to good yields.